Confession as a Means of Producing Truth and Sexuality in Michel Foucault's Philosophy / Ispovijest kao sredstvo proizvodnje istine i seksualnosti u filozofiji Michela Foucaulta - Ahmeti, Kushtrim (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
The French thinker Michel Foucault is considered as postmodernist and poststructuralist, while he regarded himself as a product of modern tradition, although his works represent a comprehensive and original critique of specifically this way of thinking. With his ideas he wanted to make a clear distinction from other prior propensities, by joining the other postmodern theorists voice, who put efforts to show the alternatives, offered by the thitherto known modern philosophical systems, as extremely humanistic. The main purpose of this paper is to examine the treatment of confession as a means of producing truth and sexuality, which takes a central place in Foucault’s works. The fact itself that he is the author of a three-volume history of sexuality says a lot about this. The interpretation will be conducted through the content analysis technique-data reduction by categorizing or reduction of any type of qualitative material in order to identify certain consistent meanings.